The creative methods of physical and health education in teacher’s work with preschool children - Kowalewski, Michał (Physical education, sport and olympism from a pedagogical perspective, 2023)
Physical activity is one of the most characteristic and natural features of the early stages of human development. Among children at the preschool age, physical development begins with spontaneous movement expression, with natural, poorly coordinated movements, which are gradually improved, often leading to excessive control or inhibition in adulthood. The civilizational progress and contemporary early education models focused on intensifying educational content mean that the youngest spend a significant part of their time sitting on a rug or at school benches. In many cases, meeting the need for exercise is limited, the role of physical education in the development of a child is marginalised, and the youngest are restricted from taking active forms of behaviour, which leads to the progressive elimination of the body's natural kinetics.The proposed creative methods of physical and health education in teacher's work with the youngest, oriented to the "creative movement", fulfil children's physical needs. Thanks to spontaneity and freedom, they allow children to express themselves creatively and support their comprehensive development, thus realising elementary paradigms, premises, and determinants characterising contemporary preschool education's primary goals and tasks.